An example of a vine-physiology based fine-scale terroir study in the AOC Lavaux-region in Switzerland - RIENTH Markus; LAMY Frederic; NOLL Dorothea; LORENZINI Fabrice; VIRET Olivier; ZUFFEREY Vivian (E3S Web of Conferences, 2018)
The aim of this ongoing study is to establish a vine physiology, berry quality - based methodology to analyze small scale differences between plots in a sub-region of the AOC Lavaux, in Switzerland. The production area Villette is almost to 100% planted with the cultivar Chasselas L. covering a total of 140 ha of steep slope terraced vineyards and offers an excellent site for terroir studies. A representative network of 23 plots covering the entire Villette production area was established in 2016 and 2017. Important differences in budburst and flowering were observed between plots whereas altitude was the main driver of precociousness. Expectedly most precious plots had highest sugar and lowest malic acid concentrations at final sampling date. Individual berry weight variation was up to 35 % at the last sampling (2.4 to 3.3 g) with variation in sugar concentration of 13 % (70-84° Oechsle). Sugar quantity per berry variation was however twice as high (26%), illustrating important differences in the sugar accumulation pattern between plots. Interestingly the latest plots accumulated highest sugar per berry with lowest concentration. The preliminary results of this ongoing study provide valuable information of the ripening potential of Chasselas in a small mesoclimate and illustrates the possibilities to characterize viticultural terroirs based on vine physiology measurements.